Description of a Working Day as a Senior Emergency Medicine Resident; Burning Candle at Both Ends! - Baratloo, Alireza; Maleki, Marzieh (Archives of Academic Emergency Medicine, 2018)
T his text is a real-time description of an emergency medicine resident’s shift in an overcrowded emergency department (ED), Tehran, Iran. It is 3:35 pm of a warm afternoon; the emergency department is filled up with ill patients. Carrying in hand the file of a patient who had three episodes of convulsive seizure, you have to writing an order for another patient with suspected pulmonary embolism.